Defect induced enhanced low field magnetoresistance and photoresponse in Pr(0.6)Ca(0.4)MnO(3) thin films - Tomi Elovaara; Sayani Majumdar; Hannu Huhtinen; Petriina Paturi (Netherlands, 2022)
We have investigated the effect of grain boundary related defects on the electronic transport properties of the colossal magnetoresistive low bandwidth manganite Pr0.6Ca0.4MnO3 (PCMO) thin films. A series of PCMO films were prepared by pulsed laser deposition method on MgO and STO substrates. Characterizations of the structural, magnetic and magneto-transport properties show that the films prepared on MgO substrate contain higher amount of structural defects and with decreasing deposition temperature an increasing amount of different crystal orientations as the level of texturing decreases. According to the low field magnetoresistance (MR) measurements, the poorly textured samples display an increased low field MR due to a grain boundary tunneling effect at low temperatures compared to the fully textured PCMO film on STO substrate. However, in spite of the level of texturing, all the samples showed a colossal magnetoresistive insulator to metal switching of almost eight orders of magnitude at low temperatures. The magnetic field required for insulator to metal transition (IMT) is much higher in PCMO samples with more structural defects. However, IMT field could be reduced over 3 T by illuminating the sample.
20th International Conference on Magnetism, ICM 2015